2004
DOI: 10.5194/acp-4-2285-2004
|View full text |Cite
|
Sign up to set email alerts
|

Alpha-pinene oxidation by OH: simulations of laboratory experiments

Abstract: Abstract. This paper presents a state-of-the-art gas-phase mechanism for the degradation of α-pinene by OH and its validation by box model simulations of laboratory measurements. It is based on the near-explicit mechanisms for the oxidation of α-pinene and pinonaldehyde by OH proposed by Peeters and co-workers. The extensive set of α-pinene photooxidation experiments performed in presence as well as in absence of NO by Nozière et al. (1999a) is used to test the mechanism. The comparison of the calculated vs me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
91
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(93 citation statements)
references
References 74 publications
2
91
0
Order By: Relevance
“…The reported values are in agreement with the quantitative struc-ture-activity relationship (QSAR) suggested by Capouet et al (i.e., (50 AE 20) % non-terminating cross-reactions for primary peroxyl radicals). [35] Interestingly, trace amounts of nopinone were detected in the product mixture. This is indeed a fingerprint for the occurrence of 1 O 2 , since the latter can, among other things, add to b-pinene to form a dioxetane that releases formaldehyde and nopinone.…”
Section: O 2 ð3þmentioning
confidence: 99%
See 1 more Smart Citation
“…The reported values are in agreement with the quantitative struc-ture-activity relationship (QSAR) suggested by Capouet et al (i.e., (50 AE 20) % non-terminating cross-reactions for primary peroxyl radicals). [35] Interestingly, trace amounts of nopinone were detected in the product mixture. This is indeed a fingerprint for the occurrence of 1 O 2 , since the latter can, among other things, add to b-pinene to form a dioxetane that releases formaldehyde and nopinone.…”
Section: O 2 ð3þmentioning
confidence: 99%
“…On the other hand, this is an elegant way of keeping the complexity under control, while, at the same time, (approximately) taking into account the effect of cross-reactions between R (b) ÀOOC and R (d) ÀOOC radicals. [35] Table 1 summarises the different reactions taken into account, together with the corresponding rate constants.…”
mentioning
confidence: 99%
“…The identification of products from α‐pinene oxidation has been well studied; however, the carbon balance of OH radical initiated chemistry cannot account for 29–46% of products . The uncertainty in product identification is related to the large number of reaction pathways of large cyclic molecules, such as α‐pinene, where simple rules deduced from well‐known reactions of smaller molecules do not necessarily apply . The wide array of products from α‐pinene oxidation implies that a single analytical technique may not be adequate for complete characterization of all α‐pinene‐derived species.…”
mentioning
confidence: 99%
“…The H-abstraction reaction pathway is generally considered as a minor channel in monoterpenes + OH reactions [14] and therefore this reaction is mostly not taken into account in reaction mechanisms. [15] However, some previous measurements by the group of Peeters in Leuven have already shown that a value of up to 30 % is possible for H-abstraction pathway for some monoterpenes + OH reactions. [18][19][20][21] Therefore, the results obtained here tend to confirm the fact that even if the addition of OH on a double bond is the main reaction channel, the H-abstraction may be significant.…”
Section: Discussionmentioning
confidence: 99%
“…If they proceed in principle through two reaction pathways (OH addition on a C=C double bond or H-abstraction with H 2 O formation), the few and scattered experimental data on H-abstraction to OH-addition in the literature led to a general consensus that OH-monoterpene reactions proceed almost exclusively by the addition channel, until the works reported by Peeter's group at Leuven. [14][15][16][17][18][19][20][21] This agreement was mainly due to the use of structure reactivity relationships (SAR) on OH + Alkene reactions [16][17] to predict monoterpene reactivity, neglecting Hatom abstraction. The few experimental measurements have shown that in some cases, H-abstraction may represent up to 30 % of the total OH reaction rate constant.…”
Section: Introductionmentioning
confidence: 98%